The Protective Effect of Pistacia vera L. (Pistachio) Against to Carbon tetrachloride (CCl4)-Induced Damage in Saccharomyces cerevisiae - Gokce, Zehra (Progress in Nutrition, 2021)
Summary. In this study, phytochemical ingredients of Pistacia vera cultivated in Kilis province, and it was investigated to demonstrate anti-oxidant effects and on some biochemical parameters and of this content on CCl4-induced cell damage in Saccharomyces cerevisiae.Pistacia vera fruits were extracted and then subjected to flavonoid analysis by HPLC device. S. cerevisiae (bread yeast) was used as a cell culture model. For the development and proliferation of S. cerevisiae FMC16 in the study, YEDP (1 g yeast extract for 100 ml, 2 g bactopeptone, 2 g glucose) medium was used.In this study, six groups were composed. i: Control group, ii: CCl4 (100 µl) group, iii: Pistacia vera 200 µl (PV2) group, iv: Pistacia vera 400 µl (PV4) group, v: PV2+CCl4 group and vi: PV4+CCl4 group. After sterilization, PV and CCl4 were inserted to S. cerevisiae cultures and the cultures were developed at 60°C for 72 hour (overnight). Antioxidant enzymes activities such as catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GSHpx), glutathione S-transferase (GST) and glutathione reductase (GR) were determined in S. cerevisiae cell by spectrophotometer.  Glutathione (GSH), oxidized glutathione (GSSG) and malondialdehyde (MDA) were investigated in S. cerevisiae cell by HPLC device.In this study, it is determined that pistachio is rich in flavonoid. Other results indicated that CCl4 application significantly increased MDA and GSSG contents the most significantly (p